PENGARUH SENAM PROLANIS TERHADAP KADAR GULA DARAH PADA PENDERITA DIABETES MELITUS TIPE II DI WILAYAH KERJA PUSKESMAS SENTOSA BARU MEDAN - Br Payung, Hotdiana; Sagala, Lam Murni (Excellent Midwifery Journal, 2024)
Type 2 diabetes mellitus is a disease in which the level of sugar/glucose in the bloodstream exceeds normal limits because the body cannot release or use insulin adequately. Objective: To determine the effect of prolanis exercise on blood sugar levels in patients with Type II DM in the Working Area of ​​the Sentosa Baru Health Center, Medan. Method: This research is quantitative with the type of experimental research and uses a sample of 65 elderly. This research uses a purposive sampling technique. Experimental tests to analyze the data in this study. Results: The results of this study indicate that there is an effect of prolanis exercise on reducing blood sugar levels in patients with type 2 diabetes mellitus with a value of p = 0.000 (<0.05).p value.000. with the value of Z p-before and after being given prolanis exercise. Conclusion: There is an effect of diabetes mellitus exercise on blood sugar levels in type 2 diabetes mellitus patients with a p-value = 0.000 which is said to have an effect ifp-value <a (0,005).